Variance Analysis of Effectiveness in Programming Language Courses - Jayamary, S.Thaddeus (International Journal of Advanced Science and Technology, 2020)
Ensuring the outcomes of Programming language courses is a taxing process in the academic environment especially during the early stages of collegiate education. Attainment of outcomes is highly influenced by levels of learners and pedagogy. Students’ level of learning differs due to several factors such as the background, medium of instruction, logical thinking, creativity and associating problems with solutions. Students need to develop programming skills for employability but the current pedagogy ignores levels of learners and their abilities in the teaching learning environment. In this regard, the authors conducted two experiments to discover the gaps based on the problems faced while teaching/learning of programming and accomplishment of learning outcomes. The results confirm that students lack higher order thinking skills and hence there is a need to update the teaching learning environment by using suitable ICT-enabled systems to teach students the programming language courses so as to ensure they achieve the learning outcomes.